Made in Mozambique - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In Maputo, the Ministry of Agriculture and Rural Development operates an agricultural MIS known as SIMA. SIMA produces a weekly bulletin Quente Quente , and a monthly report. It provides price information on 25 products in 27 producer, wholesale...